A Quasi-Experimental Study of a Web-Based English Literacy Tool for Grade 3 Students in China. (March 2021) - Gu (顾慧), Hui; Yao (姚继军), Jijun; Zhou (周龙军), Longjun; C. K. Cheung, Alan; C. Abrami, Philip
Purpose: This study explores the effectiveness of a A Balanced Reading Approach for Children Always Designed to Achieve Best Results for All (ABRACADABRA; hereinafter, ABRA)—a web-based literacy program designed by Concordia University in Canada—on third-grade students in Nanjing, China. Design/Approach/Methods: Participants comprised 999 students from three treatment schools (N = 711) and three control schools (N = 288). Three different approaches were used in the treatment schools: namely, a computer laboratory once a week, noontime study after lunch, and single-game instruction (SG) during every English lesson. Interviews were also conducted with teachers, producing qualitative data. Findings: Following 20 weeks of intervention, the overall effect size was +0.05. The SG group reflected the smallest effect size (d = -0.52). The noontime study group produced an effect size of 0.39, and the laboratory group an effect size of 0.55. This study conducted interviews with teachers to gain a qualitative understanding of the differential impacts. In doing so, this study found that teachers in the SG group were poorly motivated due to a lack of school support and heavy workload, resulting in passive roles and low ABRA program intensity. Originality/Value: The results of this study indicate that ABRA is an effective means of improving Chinese students' English literacy skills. Results also underscore the need for critical measures to encourage teachers to actively participate in the program.